Examining the Mediating Role of School Culture on the Relationship between Transformational Leadership, Teacher Commitment and Organizational Change in Elementary School - Windasari, Windasari; Roesminingsih, Erny; Sholeh, Moh; Setyowati, Sri; Hamzah, Mohd Izham bin Mohd (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study examines the mediating role of school culture on the relationship between transformational leadership, teacher commitment, and organizational change in elementary schools. This study used a quantitative Structural Equation Modeling approach to test the variable model. The subjects of this study were elementary school teachers in Surabaya city, with a total sample of 253. The research instrument used a 5 Likert scale and analyzed data using structural equation modeling. The results showed that transformational leadership and teacher commitment simultaneously and partially affect organizational change. Transformational leadership and teacher commitment also affect school culture. School culture played a role as a mediator in seeing the effect of teacher commitment on organizational change. Furthermore, school culture did not play a role as a mediator in measuring the effect of transformational leadership on organizational change.